Legal Basis of the Status of Cities in Kazakhstan - BAIZHANOVA, Kulzira; KOZHAKHMETOV, Galym; AKHMETOVA, Nailya (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018, 2019)
The article considers the important role of cities in the economic, political and cultural life of Kazakhstan, the cities are the focus of human resources, managerial ties, enterprises, housing stock, medical, cultural and educational institutions and, therefore, it discusses the necessity of legal regulation of the city status. Cities in Kazakhstan have a formal legal status of administrative-territorial unit, but there is no single legal document that identifies its legal status. This, in both theoretical and practical sense, leads to the reduction of the role of the city in the complex mechanism of managing the development of socio-economic processes. The problem of correcting of the status of the city requires special scientific-theoretical research, analysis and excursion of the progressive changes, because of the necessity of the concrete legal recommendations, methods and technologies, the maintenance and optimization of the status of the city in Kazakhstan. The article analyzes the concept of the city from a diverse perspective, identifies the legal status of the capital cities, cities of republican, regional, and district significance, provides recommendations for improving legislation and practice in this area.